Reliability of primary vein grafts in lower extremity free tissue transfers - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Free flaps transferred to the lower extremity have a higher risk of failure, which may be expected to increase further with the use of vein grafts. The results of 103 consecutive free flaps to the lower extremities of 98 patients who were operated from March 1994 to December 1999 were evaluated to assess the reliability of vein grafts in lower extremity reconstruction. Five flaps were lost and the overall success rate was 95.1%. Eighty-four free tissue transfers in 79 patients were performed for the reconstruction of traumatic cases, and 81 of these flaps were performed in a delayed manner, between 1 week and 4 months after the injury. Interpositional vein grafts were used primarily in 22 flaps-all in traumatic cases-and 21 of them survived completely (95.4%). Primary vein grafts were used both for arteries and veins in 15 flaps and for arteries only in 7 flaps. The most common cause of tissue loss in these patients was a crush injury in earthquake survivors, followed by electrical injuries, gunshot injuries, motor vehicle accidents, and chronic infections. Free muscle flaps in 13 patients, skin flaps in 4 patients, osseous flaps in 2 patients, and temporal fascial flaps in 2 patients were the flaps of choice in vein graft reconstructions. Although a higher incidence of flap loss has been reported with the use of interpositional vein grafts than with regular transfers, and the technical and pathophysiological problems in flap transfers are also high in the lower extremity, the success rate in vein-grafted free flaps did not differ from that of the simple free flap transfers in the current series. This appears to be the result of meticulous preoperative planning and proper selection of recipient vessels during optimal operative conditions.
Keywords: SINGLE CENTERS EXPERIENCE; NECK-CANCER DEFECTS; 308 FREE FLAPS; RECONSTRUCTION; HEAD; MICROSURGERY; MANAGEMENT; REPAIR; MODEL